Pendugaan Rencana Kedalaman Pengujian Standard Penetration Test (SPT) Terhadap Korelasi Data Resistivitas (Ωm) Geolistrik - Yusuf Kurniawan (Pascasarjana Teknik Sipil Institut Teknologi Nasional Malang, 2024)
Abstract— Analysis of soil bearing capacity in receiving loads is an important step in the construction of building structures, namely as a basis for planning types, materials, material quality, and foundation dimensions. This study aims to analyze the minimum resistivity (Ωm) of soil or rock material that is correlated with the Standard Penetration Test (N-SPT) value of ≥ 50. This is done as the basis for estimating the depth of drilling in the Standard Penetration Test (SPT) test. This study applies a geolytic approach to study soil and rock specifications. The research data includes descriptions of soil types, depth and thickness of each soil layer, material resistivity which is interpreted as soil density, minerals, to the presence of water content in the soil layers. The results of the data correlation analysis show that the higher the resistivity value of the soil or rock material (Ωm), the greater the number of collisions (N). The minimum resistivity value of soil material is more than (>) 121.27 Ωm obtained from the number of (N) collisions of the Standard Penetration Test (N-SPT) of more than (≥) 50. Thus, further estimation of the drilling depth can be carried out. The depth of drilling for each location varies, depending on the carrying capacity of the soil, which ultimately determines the amount of drilling costs.